Flood Risk Management in Dhaka : A Case for Eco-Engineering Approaches and Institutional Reform - World Bank (World Bank, Washington, DC, 2018)
The main objective of this study is to propose recommendations for addressing flood risks in Greater Dhaka. This is based on an analysis of flood risks facing the city, historical analysis of decision-making about flood risk management, and institutional and political economy analysis. Looking ahead, the study also considers how relatively new approaches to managing flood risk—green defense, eco-engineering, or ecosystem–based approaches— might inform the management of flood risk in Dhaka city. The study was initiated at the request of the Government of Bangladesh and carried out in close consultation with the Ministry of Environment and Forests—the focal agency for the Bangladesh Climate Change Resilience Fund (BCCRF), with the Dhaka North and South City Corporations and RAJUK. It contributes to the goals of the Country Partnership Framework 2016–20 prepared in collaboration by the Government of Bangladesh and the World Bank (World Bank 2016). At present, the World Bank is undertaking an analysis of options to engage in eastern Dhaka and also developing a broader platform for engagement in the city. The study also informs these endeavors. It is fully aligned with the preparation of the Bangladesh Delta Plan 2100, a collaborative long-term planning initiative being undertaken by Bangladesh’s Planning Commission and the Netherlands. Further, it is consistent with the Bangladesh Climate Change Strategy and Action Plan 2009, which highlights the urgency of strengthening resilience to urban flood risks.The study is based on extensive fieldwork, documentary research, and consultations with government and other stakeholders. It has the following focus areas: First, to set the stage, an analysis of flood risks facing Dhaka city is undertaken. Using publicly accessible satellite imagery, geographic information system (GIS)-based mapping tools, and available satellite-based analysis, the study assesses spatial changes in urbanization and urban ecosystems that are shaping flood risk in the city. Second, a historical analysis of flood management interventions in Dhaka and the sequence in which they occurred is undertaken. Third, an institutional and organizational capacity assessment for urban planning and flood risk management is undertaken. In proposing these recommendations, an extensive review of international experience using green defense or eco-engineering approaches was undertaken.